The Antioxidant and Xanthine Oxidase Inhibitory Activity of Plumeria rubra Flowers - Mohamed Isa, Siti Sarwani Putri; Ablat, Abdulwali; Mohamad, Jamaludin (MDPI, 2018)
Plumeria rubra Linn of the family Apocynaceae is locally known in Malaysia as “Kemboja”. It has been used by local traditional medicine practitioners for the treatment of arthritis-related disease. The LCMS/MS analysis of the methanol extract of flowers (PR-ME) showed that it contains 3-O-caffeyolquinic acid, 5-caffeoquinic acid, 1,3-dicaffeoquinic acid, chlorogenic acid, citric acid, 3,3-di-O-methylellagic acid, kaempferol-3-O-glucoside, kaempferol-3-rutinoside, kaempferol, quercetin 3-O-α-L-arabinopyranoside, quercetin, quinic acid and rutin. The flower PR-ME contained high amounts of phenol and flavonoid at 184.632 mg GAE/g and 203.2.2 mg QE/g, respectively. It also exhibited the highest DPPH, FRAP, metal chelating, hydrogen peroxide, nitric oxide superoxide radical scavenging activity. Similarly, the XO inhibitory activity in vitro assay possesses the highest inhibition effects at an IC50 = 23.91 µg/mL. There was no mortality or signs of toxicity in rats at a dose of 4 g/kg body weight. The administration of the flower PR-ME at doses of 400 mg/kg to the rats significantly reduced serum uric acid 43.77%. Similarly, the XO activity in the liver was significantly inhibited by flower PR-ME at doses of 400 mg/kg. These results confirm that the flower PR-ME of P. rubra contains active phytochemical compounds as detected in LCMS/MS that contribute to the inhibition of XO activity in vitro and in vivo in reducing acid uric level in serum and simultaneously scavenging the free radical to reduce the oxidative stress.